2004
DOI: 10.1086/427553
|View full text |Cite
|
Sign up to set email alerts
|

Search for Nonmethane Hydrocarbons on Pluto

Abstract: We have carried out infrared high-resolution spectroscopy of the Pluto-Charon system in the L band with the adaptive optics system on the Subaru telescope. The spectrum is dominated by the strong and broad absorption features of methane but includes some additional features. Comparing the spectrum with model calculations, we suggest that absorption features around 3.1, 3.2, and 3.35 mm could be an indication of nonmethane hydrocarbons on Pluto's uppermost surface. Implications of the estimated mass ratio betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…The best agreement with the data was obtained with a ternary mixture of C 2 H 2 :C 2 H 6 and CH 4 with mass ratios 1:1:10, but the narrow absorption feature of C 2 H 6 at 3.65 lm is not present in the data. Olkin et al (2007) reported observations of Pluto from 1.0 to 4.2 lm and did not find any evidence of non-methane hydrocarbons although their spectrum differed from that of Sasaki et al (2005). Differences in the spectra by Olkin et al and Sasaki et al may be explained by the fact that the central meridian longitudes represented by their observations differ by 145°.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The best agreement with the data was obtained with a ternary mixture of C 2 H 2 :C 2 H 6 and CH 4 with mass ratios 1:1:10, but the narrow absorption feature of C 2 H 6 at 3.65 lm is not present in the data. Olkin et al (2007) reported observations of Pluto from 1.0 to 4.2 lm and did not find any evidence of non-methane hydrocarbons although their spectrum differed from that of Sasaki et al (2005). Differences in the spectra by Olkin et al and Sasaki et al may be explained by the fact that the central meridian longitudes represented by their observations differ by 145°.…”
Section: Introductionmentioning
confidence: 82%
“…Later, Sasaki et al (2005) analyzed spectra of Pluto at longer wavelengths (2.9-3.9 lm) and showed that the addition of nonmethane hydrocarbons could improve the model fits to the data, but there was no clear identification. The best agreement with the data was obtained with a ternary mixture of C 2 H 2 :C 2 H 6 and CH 4 with mass ratios 1:1:10, but the narrow absorption feature of C 2 H 6 at 3.65 lm is not present in the data.…”
Section: Introductionmentioning
confidence: 99%
“…High-energy electrons produced from Saturn's magnetosphere could be partly responsible for the production of these molecules (Cravens et al 2005). Sasaki et al (2005) recently conducted a search for nonmethane hydrocarbons on Pluto and found absorptions at 3.10, 3.22, and 3.35 m (3225, 3125, and 2985 cm À1 ), whereby the peak at 3.22 m seems to be indicative of the presence of ethylene. Vernazza et al (2005) reported the presence of features appearing at 3.42 m (2920 cm À1 ) and 3.06 m (3268 cm À1 ) on the surface of the asteroid 1 Ceres, which may be indicative of the presence of ethane and acetylene, respectively.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…These non-volatile ices may subsequently be covered over time by deposition of volatiles onto the surface. Sasaki et al (2005) Grundy et al, 2010, respectively). Additionally, Cruikshank et al (2006) argue, based on currently unpublished CO laboratory data, that the contribution of 13 CO is negligible and that the 2.405 lm feature is almost entirely due to ethane absorption.…”
Section: Introductionmentioning
confidence: 97%